Economic case for intraoperative interventions to prevent surgical‐site infection. Issue 2 (January 2017) - Gillespie, B. M.; Chaboyer, W.; Erichsen‐Andersson, A.; Hettiarachchi, R. M.; Kularatna, S.
Abstract : Background: Surgical‐site infection (SSI) occurs in 1–10 per cent of all patients undergoing surgery; rates can be higher depending on the type of surgery. The aim of this review was to establish whether (or not) surgical hand asepsis, intraoperative skin antisepsis and selected surgical dressings are cost‐effective in SSI prevention, and to examine the quality of reporting. Methods: The authors searched MEDLINE via Ovid, CINAHL via EBSCO, Cochrane Central and Scopus databases systematically from 1990 to 2016. Included were RCTs and quasi‐experimental studies published in English, evaluating the economic impact of interventions to prevent SSI relative to surgical hand and skin antisepsis, and wound dressings. Characteristics and results of included studies were extracted using a standard data collection tool. Study and reporting quality were assessed using SIGN and CHEERS checklists. Results: Across the three areas of SSI prevention, the combined searches identified 1214 articles. Of these, five health economic studies evaluating the cost‐effectiveness of selected surgical dressings were eligible. Study authors concluded that the interventions being assessed were cost‐effective, or were potentially cost‐saving. Still, there is high uncertainty around the decision to adopt these dressings/devices in practice. The studies' reporting quality was reasonable; three reported at least 15 of the 24 CHEERS items appropriately. Assessment of methodological quality found that two studies were considered to be of high quality. Conclusion: With few economic studies undertaken in this area, the cost‐effectiveness of these strategies is unclear. Incorporating economic evaluations alongside RCTs will help towards evidence‐informed decisions. Abstract : Few good examples